Scientific communication in African universities : external assistance and national needs - Teferra, Damtew, 1964- (Studies in higher education, dissertation series., 2003)
One of the few current books on African higher education. Focuses on scientific research and communication on the continent. Included are chapters on scientific journals, secondary avenues of scientific communication, and funding issues.